2016
DOI: 10.4236/am.2016.717168
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for Three Coupled Nonlinear Schrödinger Equations

Abstract: In this work, we will derive numerical schemes for solving 3-coupled nonlinear Schrödinger equations using finite difference method and time splitting method combined with finite difference method. The resulting schemes are highly accurate, unconditionally stable. We use the exact single soliton solution and the conserved quantities to check the accuracy and the efficiency of the proposed schemes. Also, we use these methods to study the interaction dynamics of two solitons. It is found that both elastic and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The interaction of two solitons is discussed in detail for different parameters to produce elastic and inelastic interactions. This behavior is agreeing with [1] [2] [3] with the highest accuracy. The derived method can be used to solve similar nonlinear problems.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The interaction of two solitons is discussed in detail for different parameters to produce elastic and inelastic interactions. This behavior is agreeing with [1] [2] [3] with the highest accuracy. The derived method can be used to solve similar nonlinear problems.…”
Section: Discussionsupporting
confidence: 85%
“…In recent years the concept of soliton has been receiving considerable attention in optical communications. Since soliton is capable of propagating over long distances without change of shape and velocity, it has been found that the soliton propagating through optical fiber arrays is governed by a set of equations related to the coupled nonlinear Schrödinger equation [1] [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is noticed that there is a symmetry in momentum about d = 1, where it becomes approximately equal to zero. Therefore, the relationship between momentum and d and g is highlighted as in Figure 5, (Alamri, 2003;Ismail et al, 2016;Antikainen et al, 2012)…”
Section: Hff 318mentioning
confidence: 99%
“…However, to the best of my knowledge, effort put in T‐CNLS equation is very limited. () Aydin developed a multisymplectic scheme for N ‐coupled NLS equation with symmetric coefficients in the nonlinear terms . Ismail et al presented a splitting finite difference scheme for it which is unconditionally stable and accurate .…”
Section: Introductionmentioning
confidence: 99%
“…() Aydin developed a multisymplectic scheme for N ‐coupled NLS equation with symmetric coefficients in the nonlinear terms . Ismail et al presented a splitting finite difference scheme for it which is unconditionally stable and accurate . Liang et al studied a central difference and quadratic spline approximation‐based exponential time difference Crank‐Nicolson method .…”
Section: Introductionmentioning
confidence: 99%